2020
DOI: 10.1111/asj.13419
|View full text |Cite
|
Sign up to set email alerts
|

Importance of banana flour and its effect on growth performance of broiler

Abstract: Poultry nutrition directly influences egg and meat quality (Sugiharto et al., 2019). In the last few decades, the industrial competition in the search of better feed for poultry diet has been increased in order to maximize the sustainability of the sector and meat production (Azizi, Seidavi, Ragni, Laudadio, & Tufarelli, 2018). However, the production of adequate food is the biggest challenge for industries (Cullere et al., 2017). Many investigations have been conducted to evaluate the suitability of various f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Banana leaves contain approximately 8% polyphenols but have low levels of condensed tannins. Banana peels constitute about 30% of fresh bananas weight and banana leaves are reported to contain 85% water and 10-17% protein on a dry matter basis (Hang et al, 2018 andDumorné et al, 2020).It was determined that including 10% banana peel in poultry feed led to improved feed efficiency, feed conversion and the quality of poultry eggs and meat. However, using more than 10% banana peel in the feed could potentially decrease the growth rate of poultry (Yitbarek et al, 2019).…”
Section: Banana Wastementioning
confidence: 99%
“…Banana leaves contain approximately 8% polyphenols but have low levels of condensed tannins. Banana peels constitute about 30% of fresh bananas weight and banana leaves are reported to contain 85% water and 10-17% protein on a dry matter basis (Hang et al, 2018 andDumorné et al, 2020).It was determined that including 10% banana peel in poultry feed led to improved feed efficiency, feed conversion and the quality of poultry eggs and meat. However, using more than 10% banana peel in the feed could potentially decrease the growth rate of poultry (Yitbarek et al, 2019).…”
Section: Banana Wastementioning
confidence: 99%
“…Study has shown that unripe (green) banana flour, in addition to having a high energy (Dumorné et al., 2020 ), contains substantial amount of oligosaccharides and resistant starch (Chang et al., 2022 ). These active components are often attributed to prebiotics, which can improve intestinal ecology and function of poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Study has shown that unripe (green) banana flour, in addition to having a high energy (Dumorné et al, 2020), contains substantial amount of oligosaccharides and resistant starch (Chang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the use of UBF for broiler chicken diets is still limited. To the best of our knowledge, only Dumorné et al [7] used UBF as an energy source for broiler chickens. They confirmed that the inclusion of banana flour into broiler feeds of up to 20% did not adversely affect the growth performance of broilers [7].…”
Section: Introductionmentioning
confidence: 99%